Effect of Waxing and Gum Arabic Coating on Quality and Shelf Life of Mango (Mangifera indica L.) Fruits (University of Khartoum Journal of Agricultural Sciences, 2025)
The effect of waxing and coating with aqueous solutions of gum Arabic on quality and shelf life of the fruits of ‘Kitchner’ and    ‘Abu-Samaka’ mango fruits was evaluated. The fruits were coated with aqueous solutions of 0 %, 5 % or 10 % gum Arabic by dipping the fruits in the aqueous solution of each concentration for three minutes and air dried. In the composite treatments of gum Arabic and wax, food-grade wax was applied in a thin layer by brushing over the surface of fruits after gum Arabic treatment. The fruits were packed in carton boxes (43 x 33 x 15 cm), arranged in a completely randomized design with four replicates and stored at 18 ± 1°C and 85 % - 90 % relative humidity. Coating the fruits with gum Arabic in aqueous solutions significantly delayed the onset of the climacteric peak of respiration and fruit ripening; reduced weight loss, fruit softening, peel colour development, total soluble solids (TSS) accumulation and the drop in titratable acidity; retained ascorbic acid; maintained quality and extended shelf life of mango fruits. Waxing in addition to gum Arabic coating was more effective than gum coating alone, in all parameters studied. Gum Arabic coating at 5 % and 10 % without waxing reduced weight loss by 3.6 % and 7.7 % and peel colour development by 3.8 % and  9.6 % respectively in ‘Kitchner’  and 'Abu-Samaka', compared with the control. Gum Arabic coating at 5 % and 10 % with waxing reduced weight loss by 13.5 % and 19.6 % and peel colour by 10.5 % and 21.0 %, respectively, compared with the control. Ascorbic acid content was 5.5 % and 12.5 % more in fruits coated with gum Arabic at 5 % and 10 % aqueous solutions without waxing and 22.1 % and 33.4 % more in fruits coated with 5 % and 10 % gum Arabic with waxing in respectively in ‘Kitchner’  and 'Abu-Samaka', compared with the untreated fruits.
Keywords: Guava fruit; gibberellic acid (GA3); waxing; fruit quality